2022
DOI: 10.3389/fpsyt.2022.869106
|View full text |Cite
|
Sign up to set email alerts
|

Sustained attention induces altered effective connectivity of the ascending thalamo-cortical relay in obsessive-compulsive disorder

Abstract: Abnormal function of the thalamo-cortical relay is considered a hallmark of obsessive-compulsive disorder (OCD) and aberrant network interactions may underpin many of the clinical and cognitive symptoms that characterize the disorder. Several statistical approaches have been applied to in vivo fMRI data to support the general loss of thalamo-cortical connectivity in OCD. However, (a) few studies have assessed the contextual constraints under which abnormal network interactions arise or (b) have used methods of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 151 publications
0
1
0
Order By: Relevance
“…40 Indeed, patients with OCD exhibit deficits in spatial information memory 41,42 and visual-spatial perception, 43 consistent findings also observed among adolescent patients with OCD. 44 Recent research also has reported decreased intrinsic functional connectivity within the dorsal visual pathway 45 or the lateral visual network 46 in OCD but increased functional connectivity between the right superior lateral occipital cortex and the left lateral parietal cortex, which was positively correlated with symptom severity. 47 Additionally, selective serotonin reuptake inhibitor treatment increases metabolic activity in the right superior occipital cortex with corresponding symptomatic and neuropsychological improvements.…”
Section: Discussionmentioning
confidence: 98%
“…40 Indeed, patients with OCD exhibit deficits in spatial information memory 41,42 and visual-spatial perception, 43 consistent findings also observed among adolescent patients with OCD. 44 Recent research also has reported decreased intrinsic functional connectivity within the dorsal visual pathway 45 or the lateral visual network 46 in OCD but increased functional connectivity between the right superior lateral occipital cortex and the left lateral parietal cortex, which was positively correlated with symptom severity. 47 Additionally, selective serotonin reuptake inhibitor treatment increases metabolic activity in the right superior occipital cortex with corresponding symptomatic and neuropsychological improvements.…”
Section: Discussionmentioning
confidence: 98%